The impact of project management practice on public project success in Jimma Town, Ethiopia - Mesera, Eyuel; Fikadu Sisay, Yohannis; Ginbare Gutu, Tesfaye (Journal of Multiperspectives on Accounting Literature, 2024)
Purpose: The study aimed to examine the effect of project management practice on project success on selected public projects found in Jimma town, Ethiopia. Methodology/approach: The study was employed stratified simple random sampling techniques and total sample size of 155 was selected from public sector projects. The data were collected with self-administered questionnaires and key informant interview. The data coded and interred into the. The data were analyzed with descriptive and inferential statistics such as Mean, ANOVA, Pearson correlation and the Multiple Regression Analysis Model using SPSS software application for analysis. Findings: The results of regrssion revealed that project initiation & planning was positively and significantly associated with project success (r =0.735, ρ<0.01). Further, project execution process was positively and significantly correlated to project success (r = 0.659, ρ<0.01). Moreover, monitoring & controlling was positively and strongly correlated with project success (r = 0.747, ρ<0.01) and also there is a positive correlation between project closure & project success (r = 0.348, ρ<0.01). Practical implications: These research findings have an impact on stakeholders and policy makers regarding project management. The study recommends the introduction of effective monitoring tools and documentation in order to improve the monitoring and control process. Originality/value: The study can contribute to knowledge sharing and capacity building within Ethiopia's project management community, leading to more effective implementation of projects and improved development outcomes.